(untitled) (Research, Society and Development, 2020)
Introduction: Anatomy is fundamental for the development of medical skills and requires a lot of attention and dedication, especially about muscle’s origin and insertion. Objectives: To make the study more dynamic, attract and facilitate memorization through the development of AMDM. Methods: The activities were performed during the Anatomy practices classes of the 1º period of Medicine of UNIFAL-MG, as follows: A) Class and application of knowledge test 1; B) Formulation of origin and insertion’s table; C) Making of AMDM; D) Knowledge test 2 and application of the satisfaction questionnaire; E) analysis of the results. Results: 65 students divided into three classes were attended by the study. The 2º application of the knowledge test had a hit rate about 3 times higher than the 1º application. The students attributed significantly acceptance (89.23%) of the method used in the practical classes and suggested that they were applied to other human body’s muscle segments. Conclusion: The making of AMDM stimulates the study of anatomy and helps to supply the demands of anatomical parts, which are increasingly rare or received cadaver in anatomy laboratories.